Efficacy of beta-blockers in the treatment of sepsis (Bangladesh Journal of Pharmacology, 2021)
This meta-analysis is to systematically evaluate the efficacy and safety of beta-blockers in the treatment of sepsis. A total of 17 articles that met the inclusion criteria were included, and 10,385 cases were obtained. The meta-analysis results showed that patients with sepsis with beta-blocker usage had a significantly lower 28-day mortality. The heart rate decreased over time in patients with sepsis using beta-blocker. Moreover, central venous blood oxygen saturation increased after 24, 48, 72 hours of treatment; lactic acid and cardiac troponin I decreased after 48, 72 hours of treatment; and tumor necrosis factor-α, interleukin-1β levels decreased significantly after 12, 24, 48, 72 hours of treatment (p